Ação broncodilatadora e anti-inflamatória do 1,8-cineol em modelo experimental de asma em cobaias - Bastos, Vasco Pinheiro Diógenes (2009)
Considered as an obstructive disease of airways, asthma involves reversible processes in respiratory tree such as bronchoconstriction and airway inflammation. Therapeutic use of 1,8-cineole (eucalyptol) against this disorder have gained importance recently. This study aimed to evaluate the effects of eucalyptol on the contractile behavior of airway smooth muscle obtained from ovalbumin-sensitized and challenged guinea-pigs. We also aimed to study the effects of 1,8-cineole on pathophysiological parameters changed by airway inflammation induced by antigen challenge. We used tracheal rings which were mounted in isolated organ chambers to study its contractility. Inflammatory parameters were studied by means of histological analysis of tracheal rings, inflammatory cells counting, cytokine levels and myeloperoxidase (MPO) activity in bronchoalveolar lavage. Additionally, the inspiratory and expiratory pressures and respiratory rate of these animals were evaluated, as well as the mucociliary transport (MCT). The 1,8-cineol (6 x 10-6 to 2 x 10-2 M) decreased the basal tone of epithelium-intact tracheal rings from naïve guinea-pigs with pD2 value correspondent to 2.23 [2.10 to 2.37]. In either epithelium-removed preparations or in epithelium-intact tracheal rings pretreated with L-NAME, TEA, TTX or propranolol, no significant changes in pharmacological potency or maximal relaxant effect (Emax) induced by 1,8-cineole were observed. 1,8-cineol (6.5 x 10-6 to 6.5 x 10-3 M) significantly reversed the histamine-induced contractile response. In Ca2+-free medium maintained in presence of ACh, 1,8-cineole reduced the concentration-effect curve promoted by the addition of Ba2+, but it was ineffective when the curve was induced by adding Ca2+, an effect similar to that of verapamil. 1,8-cineole reduced the contraction induced by the antigen OVA (Schultz-Dale reaction) in tissues obtained from OVA-sensitized and OVA-challenged animals. The 1,8-cineole decreased tracheal hyperreactivity to KCl and CCh observed after antigen challenge by inhibiting selectively the concentration-effect curve induced by KCl. Pretreatment of antigen challenged animals with 1,8-cineole significantly reversed the detrimental changes in histology of the tracheal tissue, as well as changes of the MCT, which were promoted by the antigen challenge. We observed a significant reduction in the total count of inflammatory cells, especially eosinophils and neutrophils, and in the levels of IL-1, TNF-α and MPO in the bronchoalveolar lavage of challenged-animals treated with 1,8-cineole. We also observed increased expression of the anti-inflammatory cytokine, IL-10. Mast cell degranulation was inhibited in naive animals pretreated with 1,8-cineole, an effect similar to that observed with cromolyn. 1,8-cineol reversed the changes produced by antigen challenge in inspiratory and expiratory pressures and respiratory frequency. These results demonstrate that the 1,8-cineole has anti-inflammatory effect when used previously and has a relaxing action on smooth muscle of guinea pig trachea, acting preferentially in electromechanical events in smooth muscle of the airways.